Thoracoscopic management of an esophageal lung, report of a case - Santiago Correa Salazar; Ivan Dario Molina-Ramirez; Lina Eugenia Jaramillo; Mizrahim Mendez Manchola; Ana Fernanda Garces Martinez; Fernando Fierro Avila (Case Reports)
Esophageal lung is a rare broncopulmonary foregut malformation, in which the main stem bronchus arises from the esophagus. Since the description by Keely et al. in 1960, less than 25 cases have been reported. We present a case of a 4-month-old female, who was referred to our institution after 2 months of management for respiratory recurrent infections. Contrast studies were performed during the evaluation and a right broncography was identified in the esophagogram. Bronchoscopy was performed confirming the atresic right bronchus. Complementary imaging and cardiology evaluation confirmed the absence of major vascular anomalies, especially a pulmonary artery sling that has been described in relation with this entity. Due to the hypoplastic lung in the absence of major vascular anomalies, thoracoscopic pneumonectomy was deemed possible. Procedure was performed with four ports and 3 mm equipment was used. Special attention was made identifying and dissecting the vascular structures first, and then the arising esophageal bronchus was dissected. The hypoplastic lung was extracted trough a small incision inferior to the axilla.We consider that due to the hypoplastic lung and vessels, the thoracoscopic approach is safe and feasible for the management of the esophageal lung and even for de esophageal bronchus in the absence of major vascular anomalies.